EU carbon border tax: General equilibrium effects on income and emissions - Javier Flórez Mendoza; Oliver Reiter; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper employs a quantitative trade model to globally assess the implications of the EU carbon border adjustment mechanism (CBAM) on trade flows, welfare, real wages and CO2 emissions. We quantify the general equilibrium effects on EU members and non-members under various carbon tax prices, including a sector-level composition, and also compare the results to a scenario including export rebates. For the EU, we find an increase in the terms of trade and, consequently, small positive welfare effects, although there are tiny negative effects on real wages. Non-EU countries face a decline in the terms of trade and a small welfare loss as well as marginally declining real wages. Global CO2 emissions are marginally reduced, but they slightly increase in the EU due to specialisation effects.
Keywords: F11; F13; F14; F18; Q56; 330; New quantitative trade model; carbon border adjustment mechanism (CBAM); trade policy welfare; CO2 emissions